2016
DOI: 10.1007/s11748-016-0694-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the size mismatch between saphenous vein graft and coronary artery on graft patency

Abstract: A mismatch between SVG diameter and RCA diameter has an impact on the patency rate of the SVG. Evaluation of the saphenous vein before surgery and selection of a graft to minimize mismatch should improve SVG patency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
0
9
1
Order By: Relevance
“…19 A previous study reports that mismatches with diameter ratios <2.8 affected SVG patency rates and the authors diagnosed a three-year patency rate of 86.1%. 10 In our study, mismatches were detected in four patients based on a diameter ratio cut-off value of < 2.8. However, a meta-analysis shows that SVG patency rates were similar (82.3%) at 2.6 years for all SVGs, irrespective of size mismatches to the native artery.…”
Section: Intra-operative Graft Assessmentmentioning
confidence: 60%
See 1 more Smart Citation
“…19 A previous study reports that mismatches with diameter ratios <2.8 affected SVG patency rates and the authors diagnosed a three-year patency rate of 86.1%. 10 In our study, mismatches were detected in four patients based on a diameter ratio cut-off value of < 2.8. However, a meta-analysis shows that SVG patency rates were similar (82.3%) at 2.6 years for all SVGs, irrespective of size mismatches to the native artery.…”
Section: Intra-operative Graft Assessmentmentioning
confidence: 60%
“…If there was a visual suspicion of a size mismatch between the graft and native coronary artery, the diameter ratio was calculated by dividing the graft diameter by the coronary artery diameter, and a value >2.8 was considered a size mismatch. 10 All of the grafts were assessed by using transit-time flow measurement (TTFMs) after angiography and attaching all proximal anastomoses.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that when an SVG is grafted to the right coronary artery, the long-term patency rate is relatively favorable when the SVG–right coronary artery diameter ratio is ≤2.8. 18,19 In the 2016 ORACLE-NIRS study by Danek et al., 20 intravascular ultrasound and optical coherence tomography were used to evaluate SVG outcomes. The study showed that older SVGs were associated with a higher lipid core burden index and smaller lumen area and diameter, which significantly affected the long-term patency of the SVG.…”
Section: Risk Factors For Svgdmentioning
confidence: 99%
“…Regarding flow dynamics, the current understanding based on computational fluid dynamics indicates that geometric factors including anastomotic angle, shape of the distal anastomosis, and the graft-to-coronary artery diameter ratio affect graft patency 8,9) . In particular, flow turbulence resulted from the discrepancy between the graft and coronary diameter, may cause abnormal wall shear stress, which initiates intimal thickening, and resulted in graft occlusion [9][10][11] . This technique is especially artery (LITA) was used for 57 anastomoses, the right internal thoracic artery (RITA) was used for 10, RGEA was used for 4, and the radial artery was used for 1.…”
Section: Techniquementioning
confidence: 99%